Electronic Module Renewable Energy (E-MET): Validity and Practicality Aspect - Muhammad, Nurlaela; Taib, Suryani; Misbah, Misbah; Yani, Mena; Purwasih, Desy (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2022)
The study aims to describe the validity and practicality of E-MET. This research is research and development with the ADDIE model. The E-MET validator for this e-module consists of two people, consisting of academics and practising experts. The validation results using the E-MET validation sheet show that the validity of the e-module on renewable energy material has good criteria. The practicality of the developed E-MET is reviewed based on benefits, usability, and time efficiency as measured through a student response questionnaire. Then the study results show that the practicality of e-modules on renewable energy materials has good criteria. The research was conducted in class XI SMAN 3 Kota Ternate. Therefore, E-MET can be used for physics learning on renewable energy materials.Penelitian ini bertujuan untuk mendeskripsikan validitas dan kepraktisan E-MET. Penelitian ini merupakan penelitian dan pengembangan dengan model ADDIE. Validator E-MET ini e-modul berjumlah dua orang, terdiri dari ahli akademisi dan ahli praktisi. Hasil validasi menggunakan lembar validasi E-MET menunjukkan bahwa validitas e-modul pada materi energi terbarukan memiliki kriteria baik. Kepraktisan E-MET yang dikembangkan ditinjau berdasarkan aspek manfaat, kegunaan, dan efisiensi waktu yang diukur melalui angket respon peserta didik. Kemudian hasil penelitian menunjukkan bahwa kepraktisan e-modul pada materi energi terbarukan memiliki kriteria baik. Penelitian dilakukan pada kelas XI SMAN 3 Kota Ternate. Oleh karena itu, E-MET dapat digunakan untuk pembelajaran fisika pada materi energi terbarukan.Â